Ambiguity Aversion, Company Size and the Pricing of Earnings Forecasts. (7th June 2012) - Antoniou, Constantinos; Galariotis, Emilios C.; Read, Daniel
Abstract Several authors have reported an unconditional size effect in returns around earnings announcements. In this study we show how this finding can be understood as resulting from ambiguity aversion. We hypothesise that analyst forecasts for smaller companies are relatively more ambiguous; hence they are priced pessimistically by ambiguity‐averse investors. As the quarter comes to a close and ambiguity gradually subsides, the stock prices of smaller companies rise to correct this pessimism, creating the size effect. Our results support these hypotheses.